Penerapan Model Pembelajaran Window Shopping Untuk Meningkatkan Minat Belajar Fisika Siswa di SMAN 1 Pujut Lombok Tengah (Journal of Pedagogi, 2024)
This study aims to identify the application of window shopping learning model in increasing students' interest in learning at SMAN 1 Pujut. Based on the results of interviews with one of the physics teachers, it turns out that at SMAN 1 Pujut the interest in learning physics is still low. So that efforts are needed to increase students' interest in learning by applying the window shopping learning model. This model is one type of cooperative learning model that is a learning model that forms students into small groups and prioritizes the activeness of each individual in the group.